2019
DOI: 10.1177/2332858419861081
|View full text |Cite
|
Sign up to set email alerts
|

Early Elementary Science Instruction: Does More Time on Science or Science Topics/Skills Predict Science Achievement in the Early Grades?

Abstract: Recent evidence points to the early elementary grades as a pivotal point for the development of science learning trajectories and achievement gaps. Using data from the Early Childhood Longitudinal Study, this study estimates the degree to which time spent on science and the breadth of science topics/skills covered predict science achievement in the earliest grades of elementary school. Using regression along with school fixed effects and student fixed effects models, we find suggestive evidence in some models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 55 publications
0
19
0
2
Order By: Relevance
“…More specifically, only 6 of 37 studies involving elementary school students were found and included in our meta-analysis. Currently, there is growing evidence that science learning at younger age (e.g., elementary school) could be beneficial in a long term (Morgan et al, 2016 ; Curran and Kitchin, 2019 ). For example, Curran and Kitchin ( 2019 ) suggested that time spent on science instruction at younger age (kindergarten, first to third grades) could positively predict later science achievement.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…More specifically, only 6 of 37 studies involving elementary school students were found and included in our meta-analysis. Currently, there is growing evidence that science learning at younger age (e.g., elementary school) could be beneficial in a long term (Morgan et al, 2016 ; Curran and Kitchin, 2019 ). For example, Curran and Kitchin ( 2019 ) suggested that time spent on science instruction at younger age (kindergarten, first to third grades) could positively predict later science achievement.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The researchers found the results support mathematics as an accessible ground in which to integrate CT for students—particularly elementary students. Math, however, is also more often taught in elementary education than science (Curran & Kitchin, 2019). In a review of CT and mathematics, Hickmott et al (2018) found when CT concepts were discussed in the context of mathematics, the two most common mathematics domains were numbers and operations and algebra.…”
Section: Preservice Preparationmentioning
confidence: 99%
“…Science is considered as one of important subject matters in education which necessary to be taught from the lowest level of education, namely primary school (Braund & Reiss, 2019;Curran & Kitchin, 2019;Darling-Hammond et al, 2020;Faisal & Martin, 2019). Primary school is assumed as the beginning of education processes (Ferraz & Neves, 2017;Jacob & Rockoff, 2011).…”
Section: Introductionmentioning
confidence: 99%